BIBLIOMETRIC ANALYSIS FOR BEGINNERS - Aidi Ahmi (UUM Press, 2022)
Bibliometric analysis means measuring the properties of all kinds of documents, including journal articles, conference proceedings, books, etc. These properties can easily be obtained from academic databases such as Scopus. Unlike other qualitative studies, the bibliometric study requires minimal effort to get the data before it can be analysed. It will take less than five minutes to obtain the dataset if the author understands the concept. While this study initially comes from the library and information science field, it has now become popular among scholars regardless of their areas of interest. This study is suitable for anyone who wants to explore the current state of the art of the literature of any field of study. Analysis can easily be conducted using several freely available tools, such as Harzing’s Publish or Perish and VOSviewer. Unlike systematic literature review, content analysis, or meta-analysis studies, bibliometric research does not require you to download or even read the full content of the data to be analysed. This book is suitable for anyone who wants to write and publish their first paper using bibliometric analysis.